Molecular Dynamics Simulation of Oxygen Ion Conduction in Orthorhombic Perovskite Ba-Doped LaInO3 Using Cubic and Orthorhombic Model - Hwang, Kuk-Jin; Yoon, Miyoung; Hwang, Hae-Jin; Choi, Soon-Mok; Jeong, Seong-Min (AMER SCIENTIFIC PUBLISHERS, 2015)
The oxygen ion conduction behavior of an orthorhombic perovskite oxide Ba-doped LaInO3 was evaluated by molecular dynamics simulation. Comparative calculations for cubic and the orthorhombic models show that the orthorhombic model was in better agreement with the experimental results with respect to both ionic conductivity and activation energy. The results of the radial distribution function for O-O pair provided and explanation for why the ionic conductivity of cubic perovskite is higher than that of orthorhombic perovskite. The orthorhombic model has a higher peak intensity of O-O pair than the cubic model, it means that the orthorhombic model has a smaller number of oxygen-vacancy pairs in the lattice structure. Consequently, the ionic conductivity of orthorhombic perovskite is lower than that of cubic perovskite due to less conduction path.